Relative impact of early versus late design decisions in systems development. (8th August 2017) - Tan, James J. Y.; Otto, Kevin N.; Wood, Kristin L.
Abstract : To better understand the impact of early versus late design decisions, a study was undertaken on the root causes of missed requirements in new product development and their impact on development cost through rework activities. The context is the industrial development of unmanned aerial vehicles. The aim is to understand the occurrence rate of missed requirements, their root causes, and their relative impact. A quantitative approach of counting requirements changes and using engineering documentation enabled traceability from observation back to root cause origin. The development process was partitioned into sequential program segments, to categorize activities to before and after concept and design freeze. We found that there was a significant difference in the rate of design defects arising before and after concept freeze; and found there was a significantly higher number of corrective activities required for design defects arising earlier before concept freeze. The revision rate of concept phase decisions was over 50%, and the rework multiplier if detected late was over 10X. In combination, design decisions made before design freeze accounted for 86% of the total expected program cost, and 34% was determined before concept freeze. These results quantify and support the anecdotal 80–20 impact rule for design decisions.